Households' Mortgage-Rate Expectations: More Realistic than at First Glance? - Erik Hjalmarsson; Pär Österholm (Örebro University School of Business, 2017)
Household expectations of future mortgage rates elicited over the last few years might appear unrealistically low. However, taking explicit account of the high persistence in interest rates, we find that Swedish households' implied long-term expectation of mortgage rates is around 4.7 percent. This number lines up well with the long-term expectation that can be deduced from the Riksbank's assessment of the repo rate in the long run and the typical spread between the mortgage rate and the repo rate. Our analysis makes use of household mortgage rate expectations at three different horizons, which enables an explicit modelling of the "term-structure" of household forecasts.
Keywords: E40; G21; 330; Survey data; Household expectations; Mortgage rates